Pengaruh Latihan Ball Feeling dan Agillity Terhadap Kemampuan Menggiring Bola Pemain Futsal di SMP Negeri 3 Palembang - Ryvaldo Syaputra; Hetilaniar Hetilaniar; Mutiara Fajar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The problem in this study is the ability to dribble the ball in futsal games at SMP Negeri 3 Palembang is not optimal. Some of the causes of the athlete's less than optimal dribbling ability are because in dribbling, players have not been supported by good agility, coaches have never provided agility training methods that lead to these abilities, as seen by the frequent loss of the ball by athletes while being dribbled and easily taken by opponents. The population in this study were 30 extracurricular futsal students at SMP Negeri 3 Palembang. The sample in this study was 30 extracurricular futsal students at SMP Negeri 3 Palembang. The technique for taking samples in this study used Total Sampling. This research method is Experimental research, The design in this study is